Water Table Fluctuation in Tidal Lowland for Developing Agricultural Water Management Strategies - Imanudin, Momon Sodik; Armanto, Edi; Susanto, Robiyanto Hendro; Bernas, Siti Masreah (JOURNAL OF TROPICAL SOILS, 2010)
Water Table Fluctuation in Tidal Lowland for Developing Agricultural Water Management Strategies (MS Imanuddin, E Armanto, RH Susanto and SM Bernas):The research objective is to evaluate the water status in the tertiary block of tidal lowland for developing water management strategies and cropping pattern for food crop agriculture. The research was conducted in tidal lowland reclamation areas of Delta Saleh South Sumatera. The methodology used in this research was survey and monitoring. The result showed that the study area has a potential of acid sulphate soil which is indicated by phyrite layer at 60 cm below the soil surface. Variation of water table was very high in the range of 0-2 cm at rainy season and it was drop up to 90 to 100 cm below soil surface at dry season. This conditions result in the soil oxidation and the pH drop up to 2.5-3.5 (very acid). Analysis of water surplus and deficit during one year period was calculated by surplus excess water under 30 cm (SEW-30) and showed that the area study was experienced water deficit. Analysis of groundwater effect on soil moisture content showed that the critical water level was in 60 cm below soil surface. The soil moisture content at this point in the root zone was dropped into the wilting point level. It means that the water availability for crop water requirement is inadequate. For sustainable agriculture in the area study, the water table should be maintained in 50-60 cm below soil surface. Therefore, the recommendation of water management strategies in the study area is water retention in combination with control drainage system.